Consumer confidence and financial market variables in an emerging market: The case of Turkey - (:unkn) unknown (My University, 2010)
The motivation of this study is to bring together two strands of empirical research for an emerging market during the pre-crisis period; the literature on consumer sentiment and the literature on financial market variables. We propose that in emerging markets the households live close to the level of subsistence and hardly have any funds for saving purposes. Hence, they believe that the future is uncertain rather than risky. In such economies, response of households to survey questions should depend on past information and current economic outlook rather than the expectations of future paths of consumption (and growth). So, consumer sentiment should be modeled with high frequency financial market variables such as interest rates, exchange rates and the stock exchange index. We utilize this relationship for the emerging economy of Turkey. Employing weekly data for the period of January 2003 - January 2008, this study empirically shows the existence of cointegration between consumer confidence and the financial market variables of interest. Therefore, we believe that this is a significant insight for emerging markets where consumer confidence could be viewed as an endogenous variable sensitive to financial market variables rather than the future outlook of the economy. © Euro Journals Publishing, Inc.
Keywords: Cointegration; Consumer confidence; Emerging market; Financial market variables